Balamand Document (1993) — The Problem of “Uniatism” in the Theological Dialogue Between the Roman Catholic Church and the Orthodox Church - Матић, Златко (Sabornost - The Theological Year-book, 2012)
The author pays attention on the fourth document of the Joint Commission for theological dialogue between the Roman Catholic Church and the Orthodox Church. During the seventh plenary meeting (Balamand, Lebanon, June 17 to 24 1993), Commission published a document Uniatism, method of union of the past, and the present search for full communion, which contains some important practical and ecclesiological points of the present ecumenical search for full communion. The supplement brings the document translate in the Serbian language.